Boosting the Stability of Boron Peroxides through Subphthalocyanine Coordination - Labella, Jorge; López-Serrano, Elisa; Torres, Tomás (Organic Materials, 2021)
The great potential of subphthalocyanines (SubPcs) to stabilize boron peroxides has been demonstrated. In particular, a subphthalocyanato boron (III) peroxide has been prepared in good yield via boron triflate. This derivative is remarkably stable under ambient conditions and can be fully characterized. The impact of the peroxide group on the structural and optoelectronic properties of SubPc was examined by NMR and UV/Vis spectroscopies, as well as single-crystal X-ray diffraction analysis. Moreover, density functional theory calculations were performed to explain the experimental results. The reactivity of this peculiar boron peroxide as an oxidant and a Lewis base was also studied.
Keywords: subphthalocyanines; phthalocyanine analogues; boron peroxides; porphyrinoids; macrocyclic ligands